ANALISA SISTEM PENCAHAYAAN BUATAN PADA BANGUNAN SPORTHALL UNIVERSITAS INTERNASIONAL BATAM - Rangkuty, Gladies Imanda Utami; Vicalrya, Jennifer; Jesslyn, Jesslyn; Chandrawati, Vivi; Murtiono, Hendro; Suwarlan, Stivani Ayuning (Program Sarjana Arsitektur Universitas Internasional Batam, 2025)
Visual comfort in sports facilities is significantly influenced by the quality of artificial lighting systems, particularly for multi-functional buildings operating at night. This study analyzes the effectiveness of artificial lighting in the sports hall at Universitas Internasional Batam, a semi-outdoor facility serving as a sports arena, event venue, and access route to classrooms. Preliminary observations and user complaints indicated visual discomfort during nighttime activities, including uneven light distribution and excessively dark areas. The study aims to evaluate lighting level compliance with SNI 6197-2020 standards and analyze users' visual comfort perceptions. A mixed-methods approach was employed through illuminance measurements using a luxmeter and surveys of 24 active users. Results show average lighting levels of 313 lux, meeting the SNI 6197-2020 standard (300 lux) for sports facilities. However, while 70.8% of respondents rated the lighting as adequate, 54.1% experienced eye fatigue periodically due to uneven light distribution (uniformity ratio 0.60 < CIE standard 0.7) and flickering lamps (37.5% fixtures). Recommendations include regular lamp maintenance, additional lighting installation in low-intensity areas, and establishing operational procedures to ensure access corridor lights remain on for user safety and comfort. This study contributes to understanding the relationship between quantitative lighting standards and subjective visual comfort in multi-functional sports facilities.